(untitled) (Bangladesh Medical Journal, 2014)
This comparative study was conducted on patients of lateral epicondylitis attending at Physical Medicine and Rehabilitation Department of BSMMU, Dhaka from June to November 2010 with an aim to assess the effect of stretching exercise in patients of lateral epicondylitis of elbow. Eighty consecutive patients of lateral epicondylitis were randomly assigned to two groups. In group A, patients were treated with stretching exercise, ultrasound therapy (UST), NSAID, advice regarding activities of daily living. In group B, patients were treated with ultrasound therapy (UST), NSAID and advice regarding activities of daily living. The outcome was evaluated at weekly interval for 6 weeks in terms of pain, tenderness and frequency of pain. At 2nd week, the pain in group-A came to satisfactory level, but in group-B, it became so at 4th week. The improvement of tenderness was observed at 2nd and 3rd week in group A and group B respectively, but the improvement in pain frequency achieved at 2nd and 4th week in group-A and group-B respectively. The study concludes that stretching exercise is helpful in the early recovery from lateral epicondylitis, majority of the cases experiencing improvement in pain (both in terms intensity and frequency) and tenderness. DOI: http://dx.doi.org/10.3329/bmj.v43i2.21384 Bangladesh Med J. 2014 May; 43 (2): 61-66